2008
DOI: 10.1136/ard.2007.074690
|View full text |Cite
|
Sign up to set email alerts
|

Foxp3 expression in CD4+ T cells of patients with systemic lupus erythematosus: a comparative phenotypic analysis

Abstract: Our data suggest that the expression of Foxp3 on CD4(+) T cells in patients with SLE, at least to some extent, reflects the activation of CD4(+) T cells due to underlying disease activity and does not necessarily indicate a functional regulatory T cell capacity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
69
5
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 92 publications
(83 citation statements)
references
References 42 publications
8
69
5
1
Order By: Relevance
“…Our data seem to differ from those in some previous reports (9,10), but seem to be consistent with those in very recent reports (12,27), of Treg cells in human SLE. The discrepancy may be mainly due to the different definitions of Treg cells used in the different studies.…”
Section: Discussioncontrasting
confidence: 57%
“…Our data seem to differ from those in some previous reports (9,10), but seem to be consistent with those in very recent reports (12,27), of Treg cells in human SLE. The discrepancy may be mainly due to the different definitions of Treg cells used in the different studies.…”
Section: Discussioncontrasting
confidence: 57%
“…+ T cells were associated negatively with the disease activity or anti-dsDNA antibody titres in SLE patients [14][15][16]. However, recent studies have shown that FoxP3 is also expressed in some CD4 +…”
Section: Foxp3mentioning
confidence: 98%
“…Furthermore, it has been suggested by several studies that regulatory T cells (Treg), as well as its associated cytokines such as interleukin , play a pivotal role in the progression of SLE (Valencia et al 2007;Bonelli et al 2008;Tselios et al 2014;Cai et al 2015a, b).…”
Section: Introductionmentioning
confidence: 99%